Photon structure functions and azimuthal correlations of lepton pairs in tagged γγ collisions - Dova, María Teresa (1998)
The reactions e+e-→e+e-e+e- and e+e-→e+e-μ+μ-, in a single tag configuration, are studied at LEP with the L3 detector. The data set corresponds to an integrated luminosity of 93.7 pb at √s=91 GeV. Differential cross sections are measured for <mtext>1.4</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>2<mtext>≤Q</mtext>2<mtext>≤7.6</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>2. The leptonic photon structure function Fγ2 and azimuthal correlations are measured for e+e-→e+e-μ+μ-. The related structure functions FγA and FγB, which originate from interference terms of the scattering amplitudes, are determined for the first time.